Penerapan Sistem Informasi Manajemen Pendidikan di Dayah Nurul Huda Aceh Tengah - I, Ikhsan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The importance of managing information systems in every school is very important. The median benefit of the information used greatly influences the progress of promotions in schools that are being carried out. The aim of this research is to determine the implementation of the education management information system in Dayah Nurul Huda, Central Aceh. This research method is a phenomenological research method with a descriptive qualitative approach. The data sources in this research are Dayah leaders, school principals, educational staff and administrative staff. The data analysis technique in this research uses observation, interviews, documentation and literature study. The analysis technique in this research is using the miles and Huberman analysis techniques. The research results show that the management of the information system at Dayah Nurul Huda has been carried out well. Which involves online digital media as a medium for providing information from schools. The implementation of management and monitoring at Dayah Nurul Huda has been carried out well by implementing a good planning system, good organization, and implementing monitoring and evaluation as a support for the progress of management at Dayah Nurul Huda, Central Aceh. Then the Administrative Management section at Dayah Nurul Huda begins with administrative management of new student admissions, financial administration management and also management of teacher wages and honorariums which have been adjusted to their respective criteria.